Isovaleric Acidemia: A Novel Mutation with Mild Phenotype - Matalon, K.; Lombardo, R.; Fuller, K.; Matalon, R. (Journal of Nutritional Therapeutics, 2015)
Isovaleric Acidemia (IVA) is considered a severe metabolic disorder with significant morbidity and mortality. It is caused by deficiency of the enzyme Isovaleryl-CoA dehydrogenase (IVD). Early treatment with carnitine and glycine reduces the episodes of the severe metabolic crises. With the advent of neonatal screening, IVD deficiency has shown a spectrum of severity. We describe a novel homozygous mutation, R332L, in the IVD enzyme with a benign phenotype.